Components of Islamic Education - Alkindi, Jaysyur Rochman (International Journal of Global Sustainable Research, 2023)
The purpose of the study was to find out the components of Islamic education. This research uses research methodology of library research data through documents or literature materials in the form of books, magazines, historical stories, etc. The result of this study is that the components in the Islamic education system are very diverse ranging from goals, educators, learners, methods, materials and educational environments. Islamic education requires these components in supporting the learning process and each component is interrelated with each other.